2023
DOI: 10.1101/2023.02.15.528725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping Sleep’s Oscillatory Events as a Biomarker of Alzheimer’s Disease

Abstract: Objective: Memory-associated neural circuits produce oscillatory events within single-channel sleep electroencephalography (EEG), including theta bursts (TBs), sleep spindles (SPs) and multiple subtypes of slow waves (SWs). Changes in the temporal "coupling" of these events are proposed to serve as a biomarker for early stages of Alzheimer's disease (AD) pathogenesis. Methods: We analyzed data from 205 aging adults, including single-channel sleep EEG, cerebrospinal fluid (CSF) AD-associated biomarkers, and Cli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…Sleep is far from a passive state; it is a vital process for brain restoration and regulation. Inadequate sleep disrupts critical neural processes and impairs cognitive functioning (14,15). Altering these processes provides a mechanistic link through which insufficient sleep contributes to the onset or worsening of mental health, brain disorders, and chronic diseases.…”
mentioning
confidence: 99%
“…Sleep is far from a passive state; it is a vital process for brain restoration and regulation. Inadequate sleep disrupts critical neural processes and impairs cognitive functioning (14,15). Altering these processes provides a mechanistic link through which insufficient sleep contributes to the onset or worsening of mental health, brain disorders, and chronic diseases.…”
mentioning
confidence: 99%
“…An analysis of data from 205 elderly adults, including sleep EEG, Alzheimer's disease-related biomarkers in cerebrospinal fluid, and clinical dementia assessment scales, revealed that cognitive impairment was related to reduced spectral power in TBs. Individuals with normal cognition but positive for amyloid-β showed lower accuracy in the coupling of certain neural circuits, and the coupling of some neural circuits was correlated with biomarkers in cerebrospinal fluid, such as Aβ42/Aβ40, phosphorylated tau181, and total tau [13].…”
Section: Sleep Oscillations and Cognitive Impairment In Alzheimer's D...mentioning
confidence: 97%